2021
DOI: 10.1038/s41598-021-99158-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect and mechanism of vitamin D activation disorder on liver fibrosis in biliary atresia

Abstract: To investigate the mechanism of 25 hydroxyvitamin D (25(OH)D) deficiency in children with biliary atresia (BA) and its effect on liver fibrosis. The serum vitamin D and 25(OH)D, and expression of 25 hydroxylase (CYP2R1 and CYP27A1) in the liver of BA patients were detected and compared with those in the control group. We investigated the effect of differential expression of CYP2R1 in hepatocytes on the expression of genes related to liver fibrosis in primary hepatic stellate cells (HSCs) of BA and animal model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…An animal study confirmed the antifibrotic effect of 1,25(OH)2D3 (the active form of vitamin D) on the development of NAFLD by inhibiting hepatic stellate cells, thereby suppressing the expression of TGF-β and platelet-derived growth factor [20]. An important role of vitamin D deficiency in the development of NAFLD was also shown in a study on diet-induced mice model of NAFLD.…”
Section: Vitamin Dmentioning
confidence: 63%
“…An animal study confirmed the antifibrotic effect of 1,25(OH)2D3 (the active form of vitamin D) on the development of NAFLD by inhibiting hepatic stellate cells, thereby suppressing the expression of TGF-β and platelet-derived growth factor [20]. An important role of vitamin D deficiency in the development of NAFLD was also shown in a study on diet-induced mice model of NAFLD.…”
Section: Vitamin Dmentioning
confidence: 63%
“…A recent study showed that VDR acts as a possible therapeutic target for breast cancer ( 41 ). Some of these studies also suggested that VDR activation helps in the prevention of hepatic fibrosis in chronic liver injury ( 47 , 48 ). To confirm the interaction between quercetin and VDR, we conducted a molecular docking study and confirmed the interaction between quercetin and VDR.…”
Section: Discussionmentioning
confidence: 99%
“…This is the most advanced elastography technology in the world. Numerous studies have shown that TE test results exhibit a good correlation with the pathological gold standard liver fibrosis classification (34,35). It is an accurate and non-invasive method for assessing the degree of liver cirrhosis; its diagnostic sensitivity can reach 80% in children and adolescents (95% CI: 70-87%), and its specificity can reach 90% (95% CI: 84-96%) (36).…”
Section: Discussionmentioning
confidence: 99%